A thermo–chemo–mechanically coupled constitutive model for curing of glassy polymers. (July 2018) - Sain, Trisha; Loeffel, Kaspar; Chester, Shawn
Abstract: Curing of a polymer is the process through which a polymer liquid transitions into a solid polymer, capable of bearing mechanical loads. The curing process is a coupled thermo–chemo–mechanical conversion process which requires a thorough understanding of the system behavior to predict the cure dependent mechanical behavior of the solid polymer. In this paper, a thermodynamically consistent, frame indifferent, thermo–chemo–mechanically coupled continuum level constitutive framework is proposed for thermally cured glassy polymers. The constitutive framework considers the thermodynamics of chemical reactions, as well as the material behavior for a glassy polymer. A stress-free intermediate configuration is introduced within a finite deformation setting to capture the formation of the network in a stress-free configuration. This work considers a definition for the degree of cure based on the chemistry of the curing reactions. A simplified version of the proposed model has been numerically implemented, and simulations are used to understand the capabilities of the model and framework.